Analisis Indeks Paparan Radiografi Digital Pada Pemeriksaan Radiologi Thoraks Postero Anterior Sebagai Upaya Peningkatan Proteksi Radiasi Pasien - Aris Samsul (Poltekkes Kemenkes Semarang, 2022)
ABSTRACT Backgound: Digital radiography is an easy method of radiological examination, so many radiology technicians often use high exposure factors because they are considered to speed up when processing images, this can increase the risk of excessive radiation doses in patients, currently the exposure index (IE) is feedback to radiology technicians for optimal images and low doses for patients. Objective: evaluating Fujifilm (S-Value) exposure index and entrance surface dose (ESD) thorax posterior-anterior as an effort to increase patient radiation protection using the ALARA principle, Method: Data taken from samples with parameters 64 kVp 16 mAs to 94 kVp 2 mAs, ESD is measured using the thermoluminescent dosimeter (TLD) chip and exposure index (S-Value) from Fujifilm's direct radiography device. Result: The relationship between S-Value and ESD has an exponential trend graph. The rise of S-Value will be followed by the ESD sequence. With the BAPETEN reference value of surface radiation dose 0.40 mGy, the minimum S-value must be achieved so that the patient's ESD does not exceed S-532 at ESD 0.39. Conclusion: The results of this study indicate that Fujifilm's S-Value allows it to be used as an evaluation of the ESD values received by patients as an effort to increase patient radiation protection. Keywords: Exposure index (S-Value), ESD, chest radiography, radiation protection